Meningkatkan Creativepreneurship pada Siswa SMKN 4 Kabupaten Tangerang - Cahyani Kurniastuti; Ismayudin Yuliyzar; Priyo Susilo; Resy Perwithasari (Yayasan Daarul Huda Kruengmane, 2023)
Dedication to the Society with the theme Increasing Creativepreneurship in Students at SMKN 4 Tangerang Regency